2019
DOI: 10.15376/biores.14.1.1419-1434
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of action of essential oils extracted from bamboo (Phyllostachys heterocycla cv. pubescens) leaves: Chemical composition and antimicrobial activity against four food-related microorganisms

Abstract: The antimicrobial activities and potential mechanisms of natural essential oils (EOs) derived from the leaves of Phyllostachys heterocycla cv. pubescens (bamboo) against a broad range of food-borne pathogens, which included Gram-positive (Bacillus subtilis and Staphylococcus aureus) and Gram-negative (Escherichia coli) bacteria and yeast (Saccharomyces cerevisiae), were investigated. The chemical characterization of bamboo leaf essential oils (BLEOs) was determined by gas chromatography-mass spectrometry (GC-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…sector. Similar results were also observed by Tao et al [49,50]. Tanaka et al [51] reported that the active constituents in bamboo extract that inhibited the growth of S. aureus and E. coli were stigmasterol and dihydro-brassicasterol.…”
Section: Antimicrobial Activity Of Beo By Disc Diffusion Methodssupporting
confidence: 84%
See 2 more Smart Citations
“…sector. Similar results were also observed by Tao et al [49,50]. Tanaka et al [51] reported that the active constituents in bamboo extract that inhibited the growth of S. aureus and E. coli were stigmasterol and dihydro-brassicasterol.…”
Section: Antimicrobial Activity Of Beo By Disc Diffusion Methodssupporting
confidence: 84%
“…Hence, it can be concluded that BEO exhibited a broadspectrum antimicrobial activity against both Gram-positive and Gram-negative food-borne bacteria and may be explored as a promising natural antimicrobial in the food sector. Similar results were also observed by Tao et al [49,50]. Tanaka et al [51] reported that the active constituents in bamboo extract that inhibited the growth of S. aureus and E. coli were stigmasterol and dihydro-brassicasterol.…”
Section: Antimicrobial Activity Of Beo By Disc Diffusion Methodssupporting
confidence: 84%
See 1 more Smart Citation
“…It grows as a thick rod, and the surface of the stalk is covered with a layer of white powder. It is one of several vital scattered bamboo species, primarily distributed in southern China (Tao et al 2019;Yuan et al 2021). Flavonoids are secondary plant metabolites and present in nearly all parts of bamboo, such as leaves, roots, and xylem.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, many types of natural antimicrobial agents are applied in food products to avoid the use of chemical preservatives. Essential oil is one of the most interesting natural antimicrobial agents because it contains numerous natural compounds that can inhibit microbial growth (Chen et al 2014;Tao et al 2019). Application of essential oil in the vapor phase in antimicrobial packaging as a means to inhibiting mold on food has been demonstrated to be effective and harmless for humans (Tyagi et al 2012;Suhem et al 2019).…”
Section: Introductionmentioning
confidence: 99%